Fatty Acids Composition of Red and Purple Pomegranate (Punica granatum L) Seed Oil - Hartati Soetjipto; Murda Pradipta; KH Timotius (Indonesian Society for Cancer Chemoprevention, 2010)
The aim of this investigation was to determine the content and composition of fatty acid in seed oil of red and purple pomegranate (Punica granatum L). The extraction process was performed by Soxhlet extractor with petroleum ether as solvent. The separation and identification of pomegranate seed oil was done by using GCMS. The total oil content of red and purple pomegranate were 128 g/kg d.w and 103 g/kg d.w respectively. Both showed the same major fatty acids as palmitic, stearic, oleic, linoleic and punisic acid. Oleic acid (19-21%) and linoleic acid (20-21%) were found as the most dominant fatty acids in red pomegranate, whereas purple pomegranate seed oil was dominated by oleic acid (41-43%) and punicic acid (0-25%). Neutral lipid fraction of red and purple pomegranate seed oils was more dominant than glycolipid and phospholipid. Neutral lipid fraction of red and purple pomegranate seed oil were 89 % and 91% respectively. Glycolipid fraction of red and purple pomegranate seed oil were 8 % and 5 %, whereas phosholipid fraction of red and purple pomegranate seed oil were 3 % and 4 %. The punicic acid content of total lipid of purple pomegranate seed oil (PPSO) (0-25%) was higher than red pomegranate (RPSO) (9-16%). On the contrary neutral lipid of red pomegranate showed higher punicic acid content (54-75%) than the purple pomegranate (14-55%). Glycolipid of red pomegranate contained punicic acid (0-42%). The punicic acid content of the phospholipid fraction of red pomegranate was higher (0-22 %) than the one of purple pomegranate (0-2%).Key words : fatty acid, pomegranate, Punica granatum, punicic acid, seed oil